Nursing actions promoting adherence to tuberculosis treatment: scoping review - Priscila Tadei Nakata Zago; Rosana Maffacciolli; Fernanda Carlise Mattioni; Carlise Rigon Dalla-Nora; Cristianne Maria Famer Rocha (SciELO, 2021)
ABSTRACT Objective: To analyze actions promoting adherence to tuberculosis treatment that are being carried out by nurses in different countries. Method: Scoping review with selection of articles on the subject in LILACS, MEDLINE, IBECS, BDENF, SciELO, CINAHL, Embase, Web of Science, and Scopus databases. Results: Forty studies, published between 2009 and 2020, allowed the identification of nursing actions in two thematic categories. In the category "Nursing care: TB patients' specific needs to promote adherence to treatment", actions involving clinical aspects, professionals' knowledge and skills, educational and relational processes were identified. In the category "The role of nursing in coping with the social determinants of health to promote adherence to treatment", interventions related to the strengthening of family and community support, the inclusion of socioeconomic issues in care plans, and respect for cultural differences were highlighted. Conclusion: Nursing work directed to the adherence to disease treatment requires the development of technical, ethical and, above all, political skills, aiming to increase the success of the actions carried out by these professionals.